The effect of employee satisfaction on employees’ performance through organizational commitment - Triwahyuni, Ririn; Ekowati, Vivin Maharani (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2017)
This study purpose is to analyze the effect of job satisfaction and organizational commitment on performance. This research uses a quantitative approach with explanatory research type where the aim is to test between hypothesized variables. This research has hypotheses that will be tested the truth. Samples are 86 respondents. Data is collected by questionnaires and documentation. The data is analyzed by Partial Least Square (PLS). The research result indicates that job satisfaction has a direct effect on employee performance at PT Pindad (Persero). Job satisfaction has no direct effect on employee performance. Test Sobel results show organizational commitment does not mediate the effect of job satisfaction on employee performance.Keywords: job satisfaction, organizational commitment, performance